Genetic Diversity of Durian (Durio zibethinus Murr.) from North and South Nias using Simple Sequence Repeat (SSR) - Ndruru, Indah Fiyar; Saleha Hannum; Suci Rahayu (International Journal of Ecophysiology, 2023)
Durian is a tropical fruit that has economic value for Nias Island especially in North and South Nias. Anthropogenic activity already occured in Nias and caused disturbance resulting in destruction and extinction of various durian. The aim of the research was to analyzed the genetic diversity of Durian from North and South Nias using SSR primers namely: Dz844, DzGCCG01, DzGCAG01, and DzMTb021. Total DNA was successfully isolated from 20 accessions. The DNA was successfully amplified resulting in DNA alleles sizing from 170-1100 bp. All primers showed 33 alleles with 28 polymorphic bands. The DNA profile were further analyzed with Ntsys which showed that 20 accession has coefficient of similarity 0.66-0.94 and clustered into nine groups at the similarity coefficient of 0.80. The research showed that the ninth accession of durian from North and South Nias has a high genetic diversity.